Komunikasi Pembangunan dan Mekanisme Bentuk Rancangan Peraturan Desa Mengenai Tata Kelola Aset Desa - Dafis Ubaidillah Assiddiq; Mashur Hasan Bisri; Sri Handayani; Muhamad Imron; Dewi Ambarwati (Jurnal Nomosleca, 2023)
Government Regulation No. 72 of 2005 concerning Villages, where the Village Representative Body (BPD) is the embodiment of democracy development communication is essential in the administration of village governance. The method in this study uses a qualitative approach with a research focus to determine the mechanism for drafting a Village Regulation (Perdes) regarding village asset management. The results of this study include the Minister of Home Affairs Regulation Number 111 of 2014 concerning Technical Guidelines for Village Regulations, stipulating that the flow of issuing village regulations includes, a. Planning; b. Preparation (BPD/Kades); c. Discussion; d. Determination; e. Clarification.Â Â Â